AgroSalud: feeding ambitions - AgroSalud (2011)
AgroSalud is working to improve and disseminate nutritonally-improved crops to rural communities in 14 countries across Latin America and the Caribbean. This photofilm documents efforts to improve childhood nutrition through a school feeding program, which uses biofortified maize, in Colombia's southwestern department of Cauca. Agrosalud is based at the non-profit International Center for Tropical Agriculture (CIAT), also in Colombia, and is funded by a range of donors.